The color of mourning in Rome - Requena Jiménez, Miguel (Gerión. Revista de Historia Antigua, 2013)
Black is the color of mourning in ancient Rome. The presence of people in white dresses in the funerals must be interpreted as an exhibition of the legal status of the participants in the act and not as a manifestation of the mourning.